THE SIGNIFICANCE OF SUB-CRITERIA OF THE ECONOMIC IMPACT OF INTERNATIONAL SPORTS COMPETITIONS ON THE DEVELOPMENT OF PHYSICAL CULTURE AND SPORTS (Physical Culture and Sport: Scientific Perspective, 2025)
An important task of contemporary research is to determine the significance of individual sub-criteria of the economic impact of international sports events in order to develop a sound system for evaluating their effectiveness. This will make it possible to formulate evidence-based recommendations for the planning of sports events and the use of their potential for the development of physical culture and sports in Ukraine. Purpose of the study – to determine the significance of the sub-criteria of the economic impact of international sports events on the development of physical culture and sports in Ukraine and to identify the most informative indicators for a comprehensive assessment of this impact. Methods. In 2024–2025, an expert survey (n = 23) was conducted using Google Forms among specialists in the field of sports economics. Results. The growth of tourist flows and the volume of investments in sports infrastructure are the most informative sub-criteria of economic impact, confirming their long-term effect on the sector. The number of jobs created is also significant, especially for regional economic development. At the same time, revenues from advertising and sponsorship require stronger utilization to increase their impact on the economy. The most informative indicator is the total volume of investments in the construction and modernization of sports facilities, as it reflects the scale of impact and its long-term effect. The results confirm that the change in the number of tourists is the most informative indicator of the economic impact of international sports events, as it reflects the dynamics of the effect and is easily measurable. Additional tourist expenditures and the total number of visitors are important supplementary indicators, but for an objective assessment of their impact, it is necessary to take into account the structure of expenditures and long-term trends. The combined use of these indicators provides a more complete picture of the economic benefits of hosting sports events. The most informative indicator is the number of new jobs created during the organization of competitions, as it reflects both short- and long-term economic effects. New jobs in the service sector also have a high level of informativeness, as these sectors largely depend on activity during events. Jobs in the sports sector are an important indicator; however, their impact is limited by the specifics of the industry. The total volume of revenues from advertising and sponsorship is a key indicator for assessing the economic impact of international sports events, while the average income per sponsor and the number of sponsors should be used as supplementary indicators to form a comprehensive assessment of financial efficiency. Conclusion. The average investment per capita and investments in community sports programs received lower ratings due to their local nature and the complexity of assessing their real impact on physical culture and sports as a whole.
Keywords: investments; tourists; advertising; jobs